Doing Time in "The Devil's Chair:" Evaluating Nonjudicial Administrative Decisions to Isolate and Restrain Prisoners and Detainees With Mental Health Disabilities in Jails and Prisons. (November 2020) - Dorfman, Deborah A.
I address the therapeutic jurisprudence implications of nonjudicial/administrative determinations to impose restrictive behavioral interventions on individuals with mental health disabilities in the jail and prison context. Such restrictive interventions include involuntarily medications, segregation, seclusion and restraints, and other related restrictive measures. I explain why our current policies violate the basic precepts of therapeutic jurisprudence and discuss the value of introducing therapeutic jurisprudence into this process.